2023
DOI: 10.3390/jmse11081495
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Hull Structural Deformation Calculation Using the Matrix Displacement Method and Its Influence on the Shaft Alignment

Abstract: The analysis of the influence of hull deformation on shaft alignment is predominately conducted using the finite element method (FEM), which is time-consuming, labor-intensive, and challenging to use for iterative hull design optimization. In this paper, hull deformation is separated into two parts—global deformation and local deformation, simplified to a single-span beam model and a grillage beam model, respectively—then solved using the matrix displacement method (MDM). Compared to FEM, the proposed method h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…In that particular case study of the shafting system of an 82000 DWT bulk carrier, the initial alignment of the vessel was compared against the performance corresponding to different bearing offset combinations. Similar studies have been recently reported by other researchers especially focusing in the important effect of hull structural deformations in regard to shaft alignment [12][13][14].…”
Section: Introduction and Literature Trendssupporting
confidence: 88%
“…In that particular case study of the shafting system of an 82000 DWT bulk carrier, the initial alignment of the vessel was compared against the performance corresponding to different bearing offset combinations. Similar studies have been recently reported by other researchers especially focusing in the important effect of hull structural deformations in regard to shaft alignment [12][13][14].…”
Section: Introduction and Literature Trendssupporting
confidence: 88%
“…Three bearings' offset values under various conditions have been measured. The bearing reaction force can be calculated based on the offsets using the procedure described in [11]. Table 9 displays the bearing reaction forces.…”
Section: Displacement Resultsmentioning
confidence: 99%
“…The effect of rigid body displacement on shaft alignment is negligible, and it is not necessary to account for it in the testing procedure. Elastic deformation displacement refers to the global and local deformation resulting from changes in internal and external loads in the hull coordinate system [11]. Global deformation typically refers to the flexural deformation of the hull as an elongated thin-walled beam, whereas local deformation is the deformation of the local structure near the bearing as a result of the change in local pressure on the plate.…”
Section: General Plan Of the Testmentioning
confidence: 99%
See 2 more Smart Citations